2008
DOI: 10.1038/nature06781
|View full text |Cite
|
Sign up to set email alerts
|

SATB1 reprogrammes gene expression to promote breast tumour growth and metastasis

Abstract: Mechanisms underlying global changes in gene expression during tumour progression are poorly understood. SATB1 is a genome organizer that tethers multiple genomic loci and recruits chromatin-remodelling enzymes to regulate chromatin structure and gene expression. Here we show that SATB1 is expressed by aggressive breast cancer cells and its expression level has high prognostic significance (P < 0.0001), independent of lymph-node status. RNA-interference-mediated knockdown of SATB1 in highly aggressive (MDA-MB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
645
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(696 citation statements)
references
References 48 publications
43
645
4
1
Order By: Relevance
“…It reprogrammes chromatin organization and the transcription profiles of breast tumors to act as a determinant of morphogenesis and metastasis. 29 Herein, an inverse correlation was found between miR-448 and SATB1 in drug-treated breast cancer cell lines, in post-chemotherapy human breast samples, and in tumorimplanted mice. We proposed that miR-448 suppression is pivotal in the process of chemotherapy-induced EMT.…”
Section: Discussionmentioning
confidence: 97%
“…It reprogrammes chromatin organization and the transcription profiles of breast tumors to act as a determinant of morphogenesis and metastasis. 29 Herein, an inverse correlation was found between miR-448 and SATB1 in drug-treated breast cancer cell lines, in post-chemotherapy human breast samples, and in tumorimplanted mice. We proposed that miR-448 suppression is pivotal in the process of chemotherapy-induced EMT.…”
Section: Discussionmentioning
confidence: 97%
“…We found ATrich sequences being a strong positive predictor in all of the calculated models. Recently, it was reported that SATB1, the special AT-rich binding protein, is highly expressed in aggressive breast cancer cells (40). SATB1 belongs to a family of nuclear matrix binding proteins, which constitute and maintain the DNA nuclear architecture, thereby regulating cell-specific gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In primary breast tumours, high SATB1 expression was found to correlate with aggressiveness and poor clinical outcome, irrespective of lymph node status, enabling it to be considered as an independent breast cancer marker. As breast tumour growth and metastasis in mice could be prevented using RNA interference against SATB1, the protein is a potential novel target for therapy [64].…”
Section: The Role Of Nuclear Organization In Cancer 119mentioning
confidence: 99%